2005
DOI: 10.1111/j.1365-2125.2005.02391.x
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate drug prescribing in older adults: the updated 2002 Beers criteria – a population‐based cohort study

Abstract: Background In 1997, Beers and colleagues developed explicit criteria for potentially inappropriate drug prescribing in ambulatory older adults aged 65 years and over. Several studies have been performed to estimate the prevalence of inappropriate drug prescribing based on these criteria. In 2002, the criteria were updated. Aims To examine the extent and trend of inappropriate drug prescribing to ambulatory older adults in the Netherlands between 1997 and 2001, according to the 1997 and the updated Beers criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
4
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(94 citation statements)
references
References 19 publications
5
77
4
8
Order By: Relevance
“…Beers' criteria [21], suggests that STOPP may be a more relevant potential IP detection tool in primary care in Ireland than Beers' criteria, as many of Beers' criteria are redundant in the Irish setting [30]. Similarly, in a recent Dutch study it was noted that only 24 of the 78 drugs in Beers' list were available in the Netherlands [12]. Conversely, a number of the medicines in the most recent iteration of Beers' independent of diagnosis criteria are not contraindicated in older people according to the latest edition of the British National Formulary [31], e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beers' criteria [21], suggests that STOPP may be a more relevant potential IP detection tool in primary care in Ireland than Beers' criteria, as many of Beers' criteria are redundant in the Irish setting [30]. Similarly, in a recent Dutch study it was noted that only 24 of the 78 drugs in Beers' list were available in the Netherlands [12]. Conversely, a number of the medicines in the most recent iteration of Beers' independent of diagnosis criteria are not contraindicated in older people according to the latest edition of the British National Formulary [31], e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate prescription of long-acting benzodiazepines in older patients has been highlighted repeatedly in the literature over the last 25 years, in particular given the link with falls and fracture risk and the difficulties with successful withdrawal [35][36][37]. Despite this, long-acting benzodiazepines continue to be initiated and repeatedly prescribed for older patients in primary and secondary care in Ireland and other countries [10,[12][13][14]. These realities suggest that long-acting benzodiazepines should not be initiated in older patients, given their high propensity for psychological and physical dependency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In other studies that used the 2003 version of the Beers criteria, the PIMs that were most prescribed were long-action benzodiazepines, propoxyphene, amitriptyline and antihistamines. 10,12,14,27,33 Estrogen, muscle relaxants, ticlopidine, chlordiazepoxide and anti-inflammatory agents have also been cited. 12,27,33 In Brazil, Carvalho observed that anti-inflammatory agents, methyldopa, digoxin and benzodiazepines with long half-life were the PIMs most used by elderly people in the city of São Paulo.…”
Section: 212326mentioning
confidence: 99%
“…14,15 Anti-inflammatory drugs should generally be avoided in elderly patients, especially those with peptic ulcers, chronic liver or heart disease or hypertension, and individuals using drugs with antiplatelet action, such as aspirin, corticosteroids or selective serotonin reuptake inhibitors. 16,17 Many studies have indicated that the prevalence of prescribing drugs that interact with each other for patients using anti-inflammatories is very high, and of considerable concern. 18 Older people are major users of health services and subsequently of medication, including anti-inflammatory and analgesic drugs.…”
Section: Introductionmentioning
confidence: 99%